2006
DOI: 10.1128/jcm.44.5.1877-1880.2006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Liver Hepatitis C Virus Variability in Patients Coinfected with Human Immunodeficiency Virus

Abstract: Liver and plasma hepatitis C virus (HCV) variability was compared by E2 cloning and sequencing in three patients coinfected with HCV and human immunodeficiency virus (HIV) before and after interferon treatment and in three patients solely infected with HCV. The plasma and liver samples contained unique sequences. In the patients coinfected with HIV, accumulated random mutations produced mostly nonsynonymous substitutions in contrast to the reduced HCV genetic variability seen after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…Díaz Carrasco et al 5 of sequences present in plasma would be able to associate with these cells, a phenomenon called viral compartmentalization. Compartmentalized HCV sequences have been demonstrated both in immunocompromised (18,(22)(23) and immunocompetent (24)(25) individuals, and in the setting of liver transplantation (18,(26)(27). Additionally, PBMC-associated HCV sequences have also been detected after resolution of HCV infection thus indicating occult infection (28-29).…”
Section: Introductionmentioning
confidence: 99%
“…Díaz Carrasco et al 5 of sequences present in plasma would be able to associate with these cells, a phenomenon called viral compartmentalization. Compartmentalized HCV sequences have been demonstrated both in immunocompromised (18,(22)(23) and immunocompetent (24)(25) individuals, and in the setting of liver transplantation (18,(26)(27). Additionally, PBMC-associated HCV sequences have also been detected after resolution of HCV infection thus indicating occult infection (28-29).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Some differences between serum and liver quasispecies have been sought but inconsistently described. [22][23][24] The distribution of liver quasispecies may also differ when HCC and nontumoral cirrhotic liver are compared. [25][26][27][28][29][30] Finally, some articles have shown that peripheral blood mononuclear cells or hepatic lymph nodes can harbor minor or major variants not found in the serum.…”
mentioning
confidence: 99%
“…The characteristics of the four patients analyzed are expressed in Table 1. A total of 414 cloned sequences were obtained and an average of 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) sequences from each sample for both of the genomic regions analyzed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…samples. Although circulating virus is thought to represent liver population, some studies have shown evidences that plasma variants differed from those in the liver [18,19]. Moreover, a few studies have found different viral variants according to tumoral or nontumoral tissue sub-localization within the liver of HCC patients [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%